2011
DOI: 10.1309/ajcp6kffgtc8plvr
|View full text |Cite
|
Sign up to set email alerts
|

Early Lymph Node Involvement by Mantle Cell Lymphoma Limited to the Germinal Center

Abstract: Recently, several reports have described cases of "in situ" mantle cell lymphoma (MCL) in which scattered cyclin D1+ cells were present within the mantle zones of reactive-appearing lymphoid follicles. In this report, we describe an unusual histologic pattern of in situ MCL that was identified in a staging lymph node for colonic adenocarcinoma resected 4 years before a diagnosis of symptomatic MCL. Retrospective immunohistochemical studies showed scattered cyclin D1-expressing cells within otherwise reactive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…They may correspond to the circulating cells carrying the t(14;18) found in many normal individuals, and appear to have a very low malignant potential. The "in situ MCL" lesions investigated in this and other studies of individual cases 14,23,30 may correspond to a similar phenomenon. We detected the t(11;14) translocations in the eight "in situ MCL" lesions studied and in one of them we confirmed that the translocation was present in the cyclin D1-positive cells.…”
Section: Discussionsupporting
confidence: 69%
“…They may correspond to the circulating cells carrying the t(14;18) found in many normal individuals, and appear to have a very low malignant potential. The "in situ MCL" lesions investigated in this and other studies of individual cases 14,23,30 may correspond to a similar phenomenon. We detected the t(11;14) translocations in the eight "in situ MCL" lesions studied and in one of them we confirmed that the translocation was present in the cyclin D1-positive cells.…”
Section: Discussionsupporting
confidence: 69%
“…[2][3][4]40 A staging workup may also be warranted to rule out the presence of overt lymphoma elsewhere. 35 Of note, a small (<1%) monoclonal l light chainrestricted plasma cell population was also detected in our patient's bone marrow, consistent with his known MGUS. While it is tempting to speculate that this might be a facet of putative plasma cell differentiation by the MZL, this is clearly not the case given the light chain discordance.…”
Section: Dsupporting
confidence: 78%
“…Nevertheless, the availability of cyclin D1 antibodies with high sensitivity on paraffin-embedded tissues has led to the identification of rare cases of MCL either with minimal involvement of lymphatic tissues or unexpected growth patterns [6,7,9]. The two cases presented here show a very unusual "homing" to germinal centers with sparing of mantle zones and interfollicular areas, as opposed to conventional patterns of partial involvement by MCL.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, in a very recent case report [9], the presence of scattered MCL cells limited to reactive germinal centers of a morphologically hyperplastic-appearing lymph node was described and interpreted as a novel "follicular in situ" growth pattern of MCL. In this case, scattered cyclin D1-positive B cells were identified retrospectively in a staging lymph node for colonic adenocarcinoma resected 4 years before the diagnosis of symptomatic MCL.…”
Section: Discussionmentioning
confidence: 82%